Verbal cordiality and politeness - Villa Mejía, Victor (Íkala, Revista de Lenguaje y Cultura, 1999)
In our daily conversations, cordiality and politeness are part of the verbal and nonverbal interactions which constitute social actions and behaviour. With Grice’s principles and Haverkate’s politeness maxims, as a starting point, the author relates politeness to cordiality and confers them a democratic dimension as well as one of civility.